صورة الفرنسي في ثلاثية محمد ديب - سداوي, شهيرة (كلية الأدب العربي والفنون, 2025)
تتناول الدراسة تحليل صورة الفرنسي في رواية الحريق لمحمد ديب، من خلال منظور الأدب المقارن، حيث تم استعراض مفهوم الصورة الأدبية، وأنواعها، ومصادرها، مع التركيز على جدلية الأنا والآخر، ثم تم تسليط الضوء على تطور الأدب الجزائري في ظل الاستعمار الفرنسي بكل لغاته، مع دراسة تفصيلية لصورة المستوطن والسلطة الاستعمارية في الرواية. تعكس الرواية المأساة الوطنية والانكسار النفسي للشعب الجزائري في مواجهة الاحتلال، حيث تُبرز الشخصية الفرنسية بوجهين: كمستعمر ظالم وكممثل للهيمنة السلطوية، مما يعكس عمق الصراع This study analyzes the image of the French in The Fire by Mohammed Dib through the lens of comparative literature. It explores the concept of literary imagery, its types and sources, with a particular focus on the dialectic of the self and the other. The research sheds light on the development of Algerian literature under French colonialism in both Arabic and French languages. It offers a detailed examination of the portrayal of the settler and colonial authority in the novel. The Fire reflects the national tragedy and the psychological breakdown of the Algerian people under occupation, presenting the French character in two dimensions: as an oppressive colonizer and a symbol of authoritarian power, thus revealing the depth of cultural and political conflict in contemporary Algerian literature.
رواية الحريق نموذجا
Keywords: صورة الفرنسي، رواية الحريق، محمد ديب، الأدب الجزائري، الأنا والآخر.